THERMOMETER OTOMATIS BERDIRI DENGAN INTERPRETASI KONDISI TUBUH MENGGUNAKAN MICRO CONTROLLER ATMEGA 2560 DAN SENSOR MLX90614 - Nurrasyidin, Alfian Tri; Damayanti, Eva (Jurnal Mahasiswa Terapan; Vol 1 No 4 (2025): Jurnal Mahasiswa Terapan, 2025)
This tool is a tool used to measure human body temperature with a non-contact method using an atmega 2560 and an MLX90614 sensor, this tool utilizes an ultrasonic sensor to detect targets and can automatically measure without having to press a button. This tool is also equipped with a buzzer sound feature, an LED indicator and an interpretation that appears on the screen to help users understand their body condition, so they can find out whether their body temperature is low, normal or high through the interpretation displayed on the screen. The results of the analysis on the tool show that the tool can function properly. The accuracy level of this non-contact Auto thermometer reaches 98.2%. With the existence of this scientific paper module, it is hoped that it can provide convenience for users and room officers/supervisors.